Immunological aspects of the post-COVID syndrome in patients with pulmonary tuberculosis - Yu.O. Matviienko; O.R. Panasiukova (Civic Union "Communicable Diseases Intensive Care Association", 2024)
ABSTRACT. Unprecedented in human history the problem of coronavirus infection, caused by the SARS-CoV-2 virus, raised a huge amount of fundamental issues regarding the pathogenesis of the COVID-19, the interaction of the virus with the pulmonary microbioma and the immune system of human. The impact on the course of other diseases, including the tuberculosis process, remains the main theme of modernity. Among the priority areas are further search and improvement of the diagnosis of immuno-mediated disorders in patients with pulmonary tuberculosis caused by coronavirus infection, by identifying the most rational diagnostic tests of these disorders.